1973
DOI: 10.5962/bhl.part.21780
|View full text |Cite
|
Sign up to set email alerts
|

A new genus and species of microhylid frog from Ecuador

Abstract: Walker, Charles Frederic. 1973. "A new genus and species of microhylid frog from Ecuador." Occasional papers of the Museum of Natural History, the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

1987
1987
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…n. are distinguished from other Chiasmocleis species by: 1) four externally evident fingers and five toes distinguishes it from Chiasmocleis antenori , Chiasmocleis carvalhoi , and Chiasmocleis tridactyla (digit reduction; Walker 1973, Nelson 1975, Duellman and Mendelson 1995); 2) a shorter snout-vent length differentiate it from Chiasmocleis alagoanus , Chiasmocleis albopunctata , Chiasmocleis anatipes , Chiasmocleis atlantica , Chiasmocleis avilapiresae , Chiasmocleis bassleri , Chiasmocleis centralis , Chiasmocleis cordeiroi , Chiasmocleis crucis , Chiasmocleis devriesi , Chiasmocleis hudsoni , Chiasmocleis leucosticta , Chiasmocleis magnova , Chiasmocleis mehelyi , Chiasmocleis papachibe , Chiasmocleis royi , Chiasmocleis sapiranga , Chiasmocleis shudikarensis , Chiasmocleis supercilialba , and Chiasmocleis ventrimaculata (larger snout-vent length; Dunn 1949, Bokermann 1952, Walker and Duellman 1974, Caramaschi and Pimenta 2003, Cruz et al 1997, Cruz et al 1999, Caramaschi and Cruz 1997, Cruz et al 2007a, Moravec and Köhler 2007, Peloso and Sturaro 2008, Funk and Cannatella 2009, Morales and McDiarmid 2009, Peloso et al 2014); 3) small feet webbing of males and females distinguish the new species from Chiasmocleis cordeiroi , Chiasmocleis leucosticta , Chiasmocleis mantiqueira , and Chiasmocleis sapiranga (more extensive webbed feet in males and females; Cruz et al 1997, Cruz et al 2007a, b); 4) a light cream belly pattern without dark spots distinguished it from Chiasmocleis alagoanus , C . atlantica , Chiasmocleis haddadi , Chiasmocleis leucosticta , and Chiasmocleis mantiqueira (belly pattern roughly marbled in dark brown and pale cream, Cruz et al1997, Cruz et al1999, Cruz et al 2007b, Peloso et al 2014); and 5) snout rounded and belly light cream colored differentiate it from Chiasmocleis gnoma (snout truncate and belly boldly marbled in brown and pale cream; Canedo et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…n. are distinguished from other Chiasmocleis species by: 1) four externally evident fingers and five toes distinguishes it from Chiasmocleis antenori , Chiasmocleis carvalhoi , and Chiasmocleis tridactyla (digit reduction; Walker 1973, Nelson 1975, Duellman and Mendelson 1995); 2) a shorter snout-vent length differentiate it from Chiasmocleis alagoanus , Chiasmocleis albopunctata , Chiasmocleis anatipes , Chiasmocleis atlantica , Chiasmocleis avilapiresae , Chiasmocleis bassleri , Chiasmocleis centralis , Chiasmocleis cordeiroi , Chiasmocleis crucis , Chiasmocleis devriesi , Chiasmocleis hudsoni , Chiasmocleis leucosticta , Chiasmocleis magnova , Chiasmocleis mehelyi , Chiasmocleis papachibe , Chiasmocleis royi , Chiasmocleis sapiranga , Chiasmocleis shudikarensis , Chiasmocleis supercilialba , and Chiasmocleis ventrimaculata (larger snout-vent length; Dunn 1949, Bokermann 1952, Walker and Duellman 1974, Caramaschi and Pimenta 2003, Cruz et al 1997, Cruz et al 1999, Caramaschi and Cruz 1997, Cruz et al 2007a, Moravec and Köhler 2007, Peloso and Sturaro 2008, Funk and Cannatella 2009, Morales and McDiarmid 2009, Peloso et al 2014); 3) small feet webbing of males and females distinguish the new species from Chiasmocleis cordeiroi , Chiasmocleis leucosticta , Chiasmocleis mantiqueira , and Chiasmocleis sapiranga (more extensive webbed feet in males and females; Cruz et al 1997, Cruz et al 2007a, b); 4) a light cream belly pattern without dark spots distinguished it from Chiasmocleis alagoanus , C . atlantica , Chiasmocleis haddadi , Chiasmocleis leucosticta , and Chiasmocleis mantiqueira (belly pattern roughly marbled in dark brown and pale cream, Cruz et al1997, Cruz et al1999, Cruz et al 2007b, Peloso et al 2014); and 5) snout rounded and belly light cream colored differentiate it from Chiasmocleis gnoma (snout truncate and belly boldly marbled in brown and pale cream; Canedo et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…On their part Baker et al (2004) found consistent morphological and molecular differences between typical L. silvicolum and specimens of the genus from several localities in western Ecuador. Baker et al (2004) concluded that divergent specimens from western Ecuador should be included in an undescribed species they named L. aequatorialis and suggested that Colombian material previously identified as L. s. occidentalis may represent L. aequatorialis.…”
Section: Introductionmentioning
confidence: 92%
“…On their part Baker et al (2004) found consistent morphological and molecular differences between typical L. silvicolum and specimens of the genus from several localities in western Ecuador. Baker et al (2004) concluded that divergent specimens from western Ecuador should be included in an undescribed species they named L. aequatorialis and suggested that Colombian material previously identified as L. s. occidentalis may represent L. aequatorialis. Baker et al (2004) advice that at the time of their work no karyotypes or tissues were available for L. s. occidentalis, and despite the authors were allowed to extract DNA from the holotype of this taxon (Texas Cooperative Wildlife Collection -TCWC 11704), it was not possible to obtain DNA sequences, preventing molecular analyses.…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations